Beyond conventions, medication-induced organ damage: exploring a case of gangrenous cholecystitis in a healthy young adult male on fluoxetine and amphetamines - Sneed, Christina C.; Louis, Martine A.; Gratsinsky, Denis; Cervellione, Kelly (International Surgery Journal, 2023)
Acute cholecystitis occurs in 1 to 2% of patients with gallstones, with 2 to 20% progressing to gangrenous cholecystitis (GC). Within the realm of acute cholecystitis, GC presents itself as a formidable challenge, with a higher mortality rate (15 to 50%) compared to uncomplicated cholecystitis (3%) and elusive preoperative diagnosis. Traditionally observed among the elderly population burdened by comorbidities, GC’s emergence in younger patients with no apparent risk factors sets the stage for intriguing exploration. Our case report involves a healthy young adult male on fluoxetine and amphetamines, introducing the potential of medication-induced ischemia leading to the development of GC.